Pengaruh Gaya Hidup Islami, Halal Awareness, dan Korean Wave Terhadap Minat Beli Makanan Korea pada Gen Z Muslim di Kota Tangerang - Khoirunnisa Sabila; Yan Putra Timur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Islamic lifestyle, halal awareness, and the Korean wave on purchase intention toward Makanan korea among Muslim Generation Z in Tangerang City. This research employs a quantitative method using primary data collected through questionnaire distribution. The sampling technique used is purposive sampling with a total of 105 Muslim Generation Z respondents domiciled in Tangerang City. The data were analyzed using multiple linear regression analysis. The results indicate that halal awareness and the Korean wave partially have a significant effect on purchase intention toward Makanan korea, while Islamic lifestyle does not have a significant effect. However, simultaneously, Islamic lifestyle, halal awareness, and the Korean wave have a significant effect on purchase intention toward Makanan korea among Muslim Generation Z in Tangerang City.